Christmas Grace - Steele, Mindy (Parker, CO : Amara, an imprint of Entangled Publishing, LLC, 2021)
"Second chances and the Christmas spirit abound in Mindy Steel's heartwarming novel, one of faith, love, and the power of community."--
Keywords: Amish women -- Fiction; Unplanned pregnancy -- Fiction; Neighbors -- Fiction; Man-woman relationships -- Fiction; Christian fiction; Romance fiction; Christmas fiction; Novels